Design of a novel vortex-based feedback fluidic oscillator with numerical evaluation. Issue 1 (1st January 2020) - Nili-Ahmadabadi, Mahdi; Cho, Dae-Seung; Kim, Kyung Chun
ABSTRACT: In this study, a new vortex-based fluidic oscillator was designed whose performance was numerically evaluated by solving the URANS equations. The oscillator consists of a primary chamber and secondary chamber, separated by a mid-throat and connected by two feedback channels. The jet passing through these chambers forms two pairs of vortices inside the primary and secondary chambers. These vortices roll onto the jet shear layer, and gradually disturbs the jet symmetry. As a result, the vortices grow and shrink asymmetrically, activating the feedback flow to make a harmonic oscillation. The collision of the oscillating jet with the mid-throat traps a part of the jet shear layer in the primary chamber, which forms a strong vortex, returning the jet toward the other side of the mid-throat. The vortex inside the secondary chamber causes the jet to attach to one side of the secondary chamber, deviating the outlet jet to the other side. To compare the performance of the new oscillator with the original one, URANS equations were solved for two-dimensional models of both oscillators with the same grid generation and boundary conditions. The new oscillator had a higher oscillation frequency, a lower pressure drop, and a higher output momentum flux.